Relationship between health-related quality of life and respiratory health status among coal-based sponge iron plant workers in Barjora, India - Biswas, Mousumi; Chattopadhyay, Kaushik (Springer, 2017)
Background: Many coal-based sponge iron plant workers have poor health-related quality of life in general, and specifically a poor respiratory health status. However, the relationship between their health-related quality of life and respiratory health status is unknown. Aim: This study investigated the relationship between health related quality of life, measured using the EuroQol- 5D (EQ5D), and respiratory health status, measured using the St. George’s Respiratory Questionnaire (SGRQ), among coal-based sponge iron plant workers in Barjora, India. Method: A cross-sectional study was conducted among coalbased sponge iron plant workers in Barjora, and complete data were available on 252 participants. Spearman’s rank correlation coefficients were reported to show the strength of relationship between health-related quality of life and respiratory health status. Results and conclusion: Significant correlations were found between all EQ5D dimensions/visual analogue scale (VAS) and all SGRQ scores except between EQ5D-VAS and SGRQ-activity. A range of correlations was found. They were moderate between EQ5D-anxiety/depression and SGRQ-symptom, EQ5D-VAS and SGRQ-symptom, and EQ5D-anxiety/depression and SGRQ-total, but weak between all the other factors.